Formation of micro-discontinuities during thermal processing and plastic deformation of polycrystalline materials - Badiyan, E.E.; Tonkopryad, A.G.; Shekhovtsov, O.V.; Shurinov, R.V. (Functional Materials, 2008)
Influence of initial micro-defective structure and microdefects arising during thermal and mechanical treatment on mechanical characteristics of polycrystalline aluminum samples has been studied experimentally. It is shown that heat treatment of samples with strongly distorted structure results in a decreased sample density due to generation of porous structure. Formation of pores on grain boundaries hinders recrystallization and results in appearance of microcracks near the pores at plastic straining that causes the grain-boundary failure character of fine-grained samples. It is shown that pre-straining promotes decrease in porosity during high-temperature annealing that, in turn, causes coarsening of grains.